Microstructure and mechanical properties of fibre laser welded medium manganese TRIP steel. (5th October 2017) - Lun, N.; Saha, D.C.; Macwan, A.; Pan, H.; Wang, L.; Goodwin, F.; Zhou, Y.
Highlights: This manuscript presents fibre laser welding of novel medium manganese steel Dissimilar welds to high strength low alloy and dual-phase steels were achieved Heat affected zone softening was not observed in medium manganese steel Tensile joint efficiency and formability were improved by welding to dissimilar steel Graphical abstract: Abstract: Fibre laser welds of Fe-0.15C-10Mn-1.5Al medium-Mn transformation induced plasticity (TRIP) steel and its dissimilar combination with high strength low alloy (HSLA) and dual-phase (DP980) steel was assessed with respect to microstructure, microhardness, formability, and tensile properties. The fusion zone (FZ) of the medium-Mn TRIP steel weldment was consist of predominantly martensite with some interdendritic austenite due to high manganese concentration which stabilizes austenite. The FZ of dissimilar combinations to HSLA and DP980 steel consisted of mostly martensite. Microhardness profiles of the medium-Mn TRIP steel showed no indications of detrimental heat-affected zone (HAZ) softening despite the high base metal (BM) hardness (396 HV). Laser welds containing medium-Mn TRIP displayed similar FZ hardness values (413–438 HV). Failure of medium-Mn TRIP laser welds under uniaxial tension occurred adjacent to the FZ where localized strain accumulated. The tensile results showed consistent failure in the weaker BM of dissimilar joints at high joint efficiency (95–100%) with respect to the weaker material of the joint. Biaxial stretch formability of TRIP-TRIP similar welds was determined to be severely limited by the brittle FZ. Strain accumulation in the BM of HSLA and DP980 steel in dissimilar combinations improved formability of laser welded blanks containing medium-Mn TRIP steel.